The images of Arab women in selected 21st century Arab novels written in english - Jaleel, Eman Mahir (2018)
Arab women's images in contemporary Western literature are generally negative. They are often portrayed as weak and oppressed. Negative representation may hold good for some women, in limited places and periods; however, negative depiction is generalized to all women, making this issue problematic, and therefore, a befitting subject of study. The current study explores Arab women’s images in the eyes of three 21st century Arab, Western, and Arab diaspora novelists, as well as verifies whether Chandra Mohanty's (1984) reflection of Arab women's representation in Western feminist writings supports women's images in the selected novels or not. The selected novels are Zoe Ferraris’ (2010) City of Veils, Maha Gargash’s (2009) The Sand Fish, and Fadia Faqir’s (2007) The Cry of the Dove. The dominant female characters' images in these novels were examined following Mohanty's theoretical framework on Third World women's depictions in Western feminist writings. The study concludes that Arab, Western, and Arab diaspora novelists portray Arab women negatively in various domains. The female characters in the novels are depicted as weak, inferior, subordinate, marginalized, and persecuted by men. Although they are sometimes portrayed as revolutionary, their rebellion is not an indication of their being powerful; it indicates, rather, a reaction to oppression. This study verifies the eleven images of Mohanty’s framework on Third World women's depictions, which are: powerful mother, obedient wife, traditional, religious, veiled, domestic, poor, uneducated, sexually oppressed, chaste virgin, and revolutionary. The findings of this study also support Mohanty’s theory in“Under Western Eyes” (1984). However, in addition to verifying the images suggested by Mohanty vis-à-vis Arab women’s representation, the present study finds two new images of Arab women in the novels analyzed, which are: liar and immoral. The study is significant as it throws a new light on a persistent issue, that is, misrepresentation of Arab women in Western creative literature. The researcher hopes that future studies would address the Arab women's images in other literary genres, for instance, poems and plays, to add more understanding of the Arab women's images in Western literature, which may encourage Third World feminists, particularly Arab feminists, to refrain from stereotyping Arab women.